Relationship of maximum bite force with craniofacial morphology, body mass and height in an Iraqi adults with different types of malocclusion - Ghufran D Awad; Ausama A Al - Mulla (College of Dentistry/ University of Baghdad, 2014)
Background: Information concerning the maximum bite force in human population is important to clinical orthodontics. Additionally, the influence of bite force on the vertical stability of any treatment result is important. The new position of the dentition should be compatible with the dynamics of the muscular and occlusal forces in all planes. This study was conducted to 1) to measure and compare maximum bite force, body height and weight among normal occlusion and malocclusion groups (cl I,cl II,cl III) in both gender 2) to evaluate the correlation between bite force and craniofacial morphology, body height and weight. Materials and Methods: The sample consists of 100 Iraqi adult subjects aged 18-25 years. It was classified in to four groups: cl I normal occlusion, cl I malocclusion, cl II malocclusion, and cl III malocclusion according to(skeletal) the value of ANB angle and (dental)the Angle classification. Each group consist of 25 (13 male, 12 female), Maximum bite force was measured by a digital device (GM10, Naganokeiki, Japan) by putting the sensor part of occlusal force meter on first molar region, body height and weight were measured by using the Length and Weight Measuring Standard (Tanita, 2008) and craniofacial measurements were achieved by analysis of lateral cephalometric radiograph Results: The highest mean value of maximum bite force was found in normal occlusion followed by class II malocclusion and then class I malocclusion and the lowest value was found in class III malocclusion, class I skeletal relationship (cl I normal occlusion & cl I malocclusion group) had larger values of body weight when compared with skeletal class II& class III .Regarding the gender, mean values of maximum bite force and body height are higher in male than female in normal occlusion and malocclusion groups, There is a positive correlation between maximum bite force and body height and weight in normal occlusion and class I malocclusion ,there is a positive correlation between maximum bite force and palatal plane, Ramus plane, mandibular plane, posterior facial height, cranial base, dentoalveolar height, while there is a negative correlation with anterior facial height, Gonial angle, SN-Mp?,PP-MP&SN-PP? angles. Conclusion: The normal occlusion group had larger values of bite force than malocclusion group,the maximum bite force, body height is gender related, larger body build up was usually associated with larger bite force in class I skeletal relationship, Individuals with characteristics of larger maxilla ,larger mandible, larger cranial base ,short anterior facial height long posterior facial height, flat mandibular plane had the largest value of bite force.